"Mummies outside their closets". Paleoradiological investigation of Egyptian mummified remains. (September 2020) - Fusco, Roberta; Licata, Marta; Larentis, Omar; Cermesoni, Barbara; Ravagnan, Annamaria; Ciliberti, Rosagemma; Pinto, Antonio; Tesi, Chiara
Highlights: To paleoradiological investigate mummified remains from collections. To stimulate curators of small collections to contact team of anthropologists, radiologists and paleopathologists. To grant the study of finds housed in museums. To obtain more information about the anthropological cultural heritage. Abstract: Paleoradiological investigations of three mummified remains housed in the archaeological museum of Erba allowed us to investigate the origin, biological profile, embalming techniques and pathological conditions of finds unknown until now. These mummified remains, belonging to the private collection of the Majnoni family, were donated to the museum without any information about their origin. We are well aware of the past issue on the commercialization of mummified remains and of the low possibility for anthropologists to have access to ancient mummies. For this reason our intent is to stimulate curators of small collections to contact team of anthropologists, radiologists and paleopathologists to grant the study of finds housed in museums with the aim of obtaining more information about the anthropological cultural heritage.